Profil Perilaku Assertif Siswa SMP dan Implikasinya pada Layanan Bimbingan dan Konseling - Yulitri, Rina (EPIK: Edukasi Penerapan Ilmu Konseling, 2025)
Low assertive behavior in students will certainly be an obstacle for students when communicating with others. Of course, this is a serious problem, because assertive behavior has important benefits that can be experienced in students' daily lives. The purpose of this research is to see the description or profile of assertive behavior of SMPN 1 Pasaman students and its implications for counseling services. The research method used is quantitative with experimental research type, the population is 60 students. The sample of this study amounted to 13 students with strastifid simple random sampling technique. The instrument used is a questionnaire instrument using a Likert scale. The results of this study are students have assertive behavior with a high category of 6 students (10%), a high category of 18 students (30%), a medium category of 19 students (31.67%), a low category of 15 students (25%) and a very low category of 2 students (3.33%). Keywords: Group Counseling, Student Assertive Behavior